Johnston's organ and its central projections in Cataglyphis desert ants. Issue 8 (10th December 2020) - Grob, Robin; Tritscher, Clara; Grübel, Kornelia; Stigloher, Christian; Groh, Claudia; Fleischmann, Pauline N.; Rössler, Wolfgang
Abstract: The Johnston's organ (JO) in the insect antenna is a multisensory organ involved in several navigational tasks including wind‐compass orientation, flight control, graviception, and, possibly, magnetoreception. Here we investigate the three dimensional anatomy of the JO and its neuronal projections into the brain of the desert ant Cataglyphis, a marvelous long‐distance navigator. The JO of C. nodus workers consists of 40 scolopidia comprising three sensory neurons each. The numbers of scolopidia slightly vary between different sexes (female/male) and castes (worker/queen). Individual scolopidia attach to the intersegmental membrane between pedicel and flagellum of the antenna and line up in a ring‐like organization. Three JO nerves project along the two antennal nerve branches into the brain. Anterograde double staining of the antennal afferents revealed that JO receptor neurons project to several distinct neuropils in the central brain. The T5 tract projects into the antennal mechanosensory and motor center (AMMC), while the T6 tract bypasses the AMMC via the saddle and forms collaterals terminating in the posterior slope (PS) (T6I), the ventral complex (T6II), and the ventrolateral protocerebrum (T6III). Double labeling of JO and ocellar afferents revealed that input from the JO and visual information from the ocelli converge in tight apposition in the PS. The general JO anatomy and its central projection patterns resemble situations in honeybees and Drosophila . The multisensory nature of the JO together with its projections to multisensory neuropils in the ant brain likely serves synchronization and calibration of different sensory modalities during the ontogeny of navigation in Cataglyphis . Abstract : Johnston's organ is a highly sensitive mechanoreceptive organ in insect antennae. For the first time, we examined the 3D‐structure of the Johnston's organ in Cataglyphis desert ants together with its neuronal projections in the ant brain. The multisensory nature of the organ together with its targets in multimodal brain regions make the Johnston's organ an important component of the navigational toolkit in Cataglyphis ants.